2010
DOI: 10.1186/1471-2164-11-682
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and evolutionary insights into the closely-related species Streptomyces coelicolor and Streptomyces lividans deduced from high-resolution comparative genomic hybridization

Abstract: BackgroundWhilst being closely related to the model actinomycete Streptomyces coelicolor A3(2), S. lividans 66 differs from it in several significant and phenotypically observable ways, including antibiotic production. Previous comparative gene hybridization studies investigating such differences have used low-density (one probe per gene) PCR-based spotted arrays. Here we use new experimentally optimised 104,000 × 60-mer probe arrays to characterize in detail the genomic differences between wild-type S. livida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 65 publications
1
40
0
Order By: Relevance
“…Genomic hybridization experiments using an S. coelicolor M145 microarray and DNA from different S . lividans strains, showing the absence of several S. coelicolor genes from S. lividans , have also been reported (Jayapal et al 2007; Lewis et al 2010). Most of these genes are clustered within genomic islands, although it was also concluded that genetic variation among these strains might actually span throughout the entire chromosome (Lewis et al 2010).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Genomic hybridization experiments using an S. coelicolor M145 microarray and DNA from different S . lividans strains, showing the absence of several S. coelicolor genes from S. lividans , have also been reported (Jayapal et al 2007; Lewis et al 2010). Most of these genes are clustered within genomic islands, although it was also concluded that genetic variation among these strains might actually span throughout the entire chromosome (Lewis et al 2010).…”
Section: Introductionmentioning
confidence: 81%
“…lividans strains, showing the absence of several S. coelicolor genes from S. lividans , have also been reported (Jayapal et al 2007; Lewis et al 2010). Most of these genes are clustered within genomic islands, although it was also concluded that genetic variation among these strains might actually span throughout the entire chromosome (Lewis et al 2010). A good quality S. lividans genome sequence from a parental strain should provide further insights into the evolutionary processes leading to these intriguing genotypic and phenotypic differences.…”
Section: Introductionmentioning
confidence: 81%
“…Recently, the ethylmalonyl-CoA pathway, which operates in ecologically relevant species, such as many alphaproteobacteria (Methylobacterium, Rhodobacter) and actinomycetes (Streptomyces), was discovered (41,44,79,92,110). In this acetylCoA assimilation strategy, two carboxylation reactions occur.…”
Section: Carboxylases In Assimilatory Pathwaysmentioning
confidence: 99%
“…S. coelicolor and Streptomyces lividans both display a distinct dependence on copper for development with that of S. lividans being more pronounced (18). They also share a high level of sequence identity and genome organization (19,20), and the gene numbering of the S. coelicolor genome database is used for S. lividans in this study. Sequence alignment of the S. lividans 4136 gene product with known CsoR orthologues reveals conservation of the amino acids that act as Cu(I)-binding ligands and two amino acids considered important for the Cu(I)-dependent allosteric regulation of DNA binding (Fig.…”
mentioning
confidence: 99%